Specifying Resistance Distance and Ratio for Special Strength Test in 1500 m Youth Running - Awadd, Ali; Abdulameer, Eman (Journal of Physical Education, 2021)
The research aimed at specifying distance and ratio of resistance for special strength endurance in 1500m youth running. The researchers used the descriptive method on (30) youth runners from the national center for gifted in Athletics. Three tests were specified and a pilot study was applied to come up with the conclusions and recommended generalizing the distances and ratios specified to test and train special strength endurance for 1500m youth running as well as using these tests for special strength endurance for continuous evaluation of runners and for runner’s selections.